Cyrano [videorecording (DVD)] - Schmidt, Erica; Dinklage, Peter; Bennett, Haley, 1988-; Harrison, Kelvin, Jr., 1994-; Mendelsohn, Ben; Salahuddin, Bashir, 1976-; Dolan, Monica; Dessner, Aaron; Dessner, Bryce; McGarvey, Seamus, 1967- (Universal, 2022)
A man ahead of his time, Cyrano de Bergerac dazzles whether with ferocious wordplay at a verbal joust or with brilliant swordplay in a duel. But, convinced that his appearance renders him unworthy of the love of a devoted friend, the luminous Roxanne, Cyrano has yet to declare his feelings for her, and Roxanne has fallen in love, at first sight, with Christian.